Analysis Of Thrift Ball Sale And Purchase Practices From The Perspective Of Islamic Economic Law - Zumara Najla Azzahra (Journal of World Science, 2025)
This research aims to analyze the practice of buying and selling contracts in thrift ball businesses from the perspective of Islamic economic law. Thrift ball, or the sale of imported second-hand clothing in bulk, has become an increasingly popular business phenomenon in Indonesian. This practice raises various legal issues, including compliance with Sharia principles that emphasize fairness, transparency, and legality in transactions. This study uses a normative approach with case study methods and conceptual approaches, where data is collected through in-depth interviews, observations, and analysis of related documents. The results of the study show that although there are some violations of Sharia principles, such as unclear information regarding the condition of the goods and their origin, this practice can be adjusted to better align with Sharia provisions.